الصور الإيقاعية والجمالية في ديوان مزاجها زنجبيل: دراسة تحليلية بلاغية - د. وداعة عبد الله علي سرَّار (White Nile Journal for Studies and Research, 2023)
Literature is the mirror that enables us to know the past and present as well as future. Therefore, the study tackles El –Laboon’s book of poetry as a field of the study focusing on the aesthetical and rhythmical aspects. The study aims at recognizing the rhythms in the book. The study adopted the descriptive analytical methods. The study found out a lot of results, some of them are: El –Laboon’s book of poetry has no poems of free verse , the simple meter is the most used ones in his book of poetry, the letters (ta-and Ra ) are the most repetitive in the first book of poetry 67-15 % and other percentage is 16-49% for each letter. The siple meter is the highest percentage of the meters, the ration is 73-93 . also it is the highest directed ration which is 37-53%. Also the study found out that there are 43 poems not 42 as has been mention in the table of contents in his book of poetry . the study recommends that the literary works of the modern poets should be read and to reveal their abilities to write poetry and analyze it practically so as to be added to is available .